The position of the " Freedom Orbit" component in the Quranic Theory of Freedom - Eshagh Soltani (رهیافتهای سیاسی و بین المللی)
This article intends to explain the point that by presenting the basic questions in the field of freedom to the Holy Qur'an, the existence of distinct components can be extracted from the answers reflected in various verses, which is interpreted as the " Freedom Orbit ". The present study is based on the method of "Thematic Interpretation of the Holy Quran" and after identifying the existence of the component of freedom orbit, explains its content and introduces the element of "Truth" as the orbit of freedom in the Holy Quran. Accordingly, the element that provides the conditions necessary for human enjoyment of freedoms in worldly life and determines the instances of freedoms and non-freedoms is " Truth ". Truth has always been a fixed and lasting thing that, due to its roots in human nature, brings order and peace to human society; Because the truth is the only criterion for measuring the actions of individuals and judging between them to eradicate differences. Such a special work is due to the fact that the truth is only from God Almighty and derives only from the essence of the transcendent burden.